Samoczynna renaturyzacja obszarów nadmiernej eksploatacji gospodarczej w Sudetach - pojęcie, formy, przyczyny i skutki - Czaja, Stanisław (Self-renaturisation of the high-economic-exploitation-lands in Sudetes mountains region - notion, forms, causes and results, 2006)
The article presents forms of anthropopressure (part 1) and notion and forms of renaturisation (part 2). The third part includes examples of self-renalurisalion in the Sudetes Region. In the fourth part the author presents the foundation of economic evaluation of ecological processes of self-renaturisation in the Sudetes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 70-84